Influence of the secondary emission coefficient on plasma characteristics in an electron gun with inductive excitation (Civil Engineering Science, 2026)
This study investigates the influence of the secondary electron emission coefficient () on plasma parameters in an electron gun with inductive excitation. A two-dimensional axisymmetric model was developed in COMSOL Multiphysics, incorporating key processes such as electron impact ionization, argon excitation, plasma heating by RF fields, and secondary electron emission. The emission coefficient was varied from 0 to 0.2, revealing notable effects on plasma behavior. As increased, electron density near the cathode center decreased by approximately 11 %, while the overall ion density grew by about 10 %. Opposite trends were observed in current distributions: the central electron current increased by 11 %, whereas the ion current moderately decreased. A numerical artifact near the symmetry axis was identified and interpreted accordingly. The results confirm the model’s physical consistency and its potential as a basis for simulating combined inductive-magnetron systems. Future work will focus on incorporating magnetron excitation to explore interactions between distinct excitation mechanisms and their impact on plasma structure.
Keywords: induction-magnetron excitation; cold cathode; hybrid plasma systems; optimization of plasma parameters